The multiplicity of jobs of the urban-poor breadwinning fathers in Iloilo City - Ardales, Feb Grace Liberal .; Yudelmo, Ma. Leah Eguilos (1998.)
The worsening socio-economic condition of the society serve as a reason why the urban poor breadwinning fathers are engaging in the multiplicity of jobs. It is treated by the breadwinning fathers as a means for them in satisfying the basic needs of the family. It is also necessary to consider proper time management to avoid overlapping of activities and time constraints., The study of the multiplicity of jobs of the breadwinning fathers in Iloilo City revolves in the description of the socio-economic condition of the families of the urban poor breadwinning farthers who have multiple jobs in Iloilo City. It is also concern in determining the different kinds of jobs these urban-poor breadwinning fathers are engage in as well as the reasons why they engage in such multiplicity of jobs. Finally, the last that is very necessary is the analysis of how they manage their time in each of their job and their personal activities.
Research Paper (Undergraduate, Bachelor of Arts in Community Development) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.